2017
DOI: 10.1504/ijima.2017.082988
|View full text |Cite
|
Sign up to set email alerts
|

Message and source characteristics as drivers of mobile digital review persuasiveness: does cultural context play a role?

Abstract: This study examines the impacts of message valence (positive/ negative/sided) and perceived source similarity on user attitudes towards mobile restaurant reviews and review persuasiveness in low-and high-context cultures. Two experiments were conducted in the USA and Ukraine. The results reveal significant differences in consumer paths to adopting mobile digital reviews in low-context vs. high-context cultures. They indicate that in low-context cultures positive reviews are perceived as more trustworthy, credi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Several studies confirm that review valence influences review credibility (Lee and Koo 2012;Hong and Pittman 2020;Lo and Yao 2018;Manganari and Dimara 2017;Pentina et al 2018;Pentina et al 2017;vanLohuizen and Trujillo-Barrera 2019;Kusumasondjaja et al 2012;Lim and Van Der Heide 2015;Chiou et al 2018). Chiou et al (2018) explain review valence is negative or positive evaluation of the product or service in online reviews.…”
Section: Review Characteristicsmentioning
confidence: 91%
See 2 more Smart Citations
“…Several studies confirm that review valence influences review credibility (Lee and Koo 2012;Hong and Pittman 2020;Lo and Yao 2018;Manganari and Dimara 2017;Pentina et al 2018;Pentina et al 2017;vanLohuizen and Trujillo-Barrera 2019;Kusumasondjaja et al 2012;Lim and Van Der Heide 2015;Chiou et al 2018). Chiou et al (2018) explain review valence is negative or positive evaluation of the product or service in online reviews.…”
Section: Review Characteristicsmentioning
confidence: 91%
“…Tversky and Kahneman (1991) explain that loss-framed arguments have a greater impact on the behaviour of consumer than gain-framed arguments. Contradictory to these findings, a few studies found that positive reviews are more credible than negative reviews (Hong and Pittman 2020;Pentina et al 2017Pentina et al , 2018. Lim and Van Der Heide (2015) found that though negative reviews impact greatly on consumer behavior it is perceived to be less credible.…”
Section: Review Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation